(untitled) (Al-Qamar, 2019)
Labours, ironically, have been depriving badly from their rights even by the developed countries. Owing this situation various laws, rules and regulations about labours are added to the legal spectrum of various countries. Pakistan, also has taken steps in this regard. Islamic Sharīʻah unlike the conventional system has envisaged labours’ rights from the very beginning. Quran, Ḥadīth and Fuqahā have discussed labours’ rights with minute details. The present paper, aims to critically analyze and compare the labours’ rights in Pakistan with those offered by Sharīʻah. Findings show that majority of such rights given by Sharīʻah to the labours, are inculcated in the legal system of Pakistan. However, still there is room for further upgrading. So the present work suggests improvements in this regard.